Traumatic Page Kidney Induced Hypertension in Critical Care: Immediately Resolved or Long-Term Resistant Problem - E. Brotfain; L. Koyfman; A. Frenkel; A. Smolikov; A. Zlotnik; M. Klein (Case Reports in Critical Care)
Page kidney is a well-known phenomenon causing hypertension, due to compression of renal parenchyma by a subcapsular hematoma, of either traumatic or non-traumatic origin. The main therapeutic approach is based on surgical approach (nephrectomy or hematoma evacuation) and antihypertensive treatment. In this paper we present a post-traumatic case of Page Kidney in a Critical Care unit. We discuss different therapeutical opportunities to extremely elevated systemic blood pressure resistant to traditional drug therapy.